The system dynamic model of the labor migrant policy in economic growth affected by COVID-19 - S. Kozlovskyi; D. Bilenko; M. Kuzheliev; R. Lavrov; V. Kozlovskyi; H. Mazur; A. Taranych (Global Journal of Environmental Science and Management)
At the end of 2019, the new virus called Coronavirus Disease (Covid-19) spread widely from China all over the world. In March 2020 the World Health Organization declared a new virus outbreak as “a global pandemic”, and recommended social distancing and quarantine. Most countries in Europe have been quarantined. The social aspect of this issue is complicated by the fact that Europe nowadays hosts 82 million international migrants. If migrant workers leave the host country, it reduces the Covid-19 spread. Nevertheless, if migrant workers do not return, it will worsen the situation with the economic crisis. The subject of the study is the instrumental and mathematical aspects of impact simulation of labor migrants’ policy on the economic growth of the host country affected by COVID-19 pandemic. The aim of the work is to develop the system dynamics model for assessing labor migrants’ policy impact on the economic growth of the host country during COVID-19 pandemic. It examined through hypotheses of different scenarios of labor migrants policy impact on the host country economic growth in Covid-19 pandemic. The proposed model combines epidemiological and the economic growth models and relies upon real statistical data. The analysis was carried out in four European countries. The results of the study enabled to state that without migrant workers the gross domestic product may fall to 43% in Italy, 45% in Netherlands, 37% in Spain and 200% in Switzerland in 2020.